LUCIANO BOI, ANDREA CANNAS, LUCA VARGIU (eds.) - Abitare. Approcci interdisciplinari e nuove prospettive - Salvo, Simona (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Luciano Boi, Andrea Cannas, Luca Vargiu (eds.) Abitare. Approcci interdisciplinari e nuove prospettive Cagliari: UNICApress, 2019. 173 pp. Softcover. Language: Italian. Open access ISBN: 978-88-3312-009-6